Invisibility of Whiteness: A Homiletical Interrogation (Homiletic, 2021)
This article examines the invisibility of whiteness in homiletics which operates in and beyond homiletics. One example is that white authors still rarely self-locate in their academic writing. White scholars’ lack of self-location is juxtaposed with BIPOC scholars’ pressure to self-declare. Another example is that the work done by racialized scholars is parceled out as specialized, resulting in further marginalization, while white scholars’ work is universalized and centralized. A further issue that teachers of homiletics must be conscious of is how we select (i.e., choose and omit) readings for students as well as how to arrange the chosen readings beyond white normative ways. Once the reality of whiteness in the field of homiletics is made visible, preaching practices and consideration of environments including preaching place and worship space are examined. The article argues how influential the preaching place is. In a similar vein, it interrogates the use of art in worship and the location of the pulpit as it conveys whiteness. The article further probes the symbolism of color that is embedded not only in visible art but in language, especially within the text of the Bible. Two stories in the Bible from the book of Ruth and Genesis will be discussed as a homiletical interpretive task of making whiteness visible.